Tsiklovoi kontrol' kachetva sudeistva v sportivnoi gimnastike - Petrov, L. N. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study was to elaborate the method of cyclic control in sports gymnastic competitions' refereeing. The data of 13 championships of the previous olympic cycles had been investigated. As a result there had been obtained the separate and integrative qualitive and quantitive characteristics of referee groups by the signs of their complement, qualification, special preparadeness and representativity with their integrative evaluation, and characteristics of referee's quality.